Nigrostriatal dopamine transporter availability in early Parkinson's disease - Fazio, Patrik; Svenningsson, Per; Cselényi, Zsolt; Halldin, Christer; Farde, Lars; Varrone, Andrea (Movement disorders, 2018)
ABSTRACT Background: The imaging of biomarkers for characterization of dopaminergic impairment in Parkinson's disease (PD) is useful for diagnosis, patient stratification, and assessment of treatment outcomes. [18F]FE‐PE2I is an improved imaging tool allowing for detailed mapping of the dopamine transporter protein in the nigro‐striatal system at the level of cell bodies (substantia nigra), axons, and presynaptic terminals (striatum). Objectives: The objective of this study was to compare the dopamine transporter protein loss in the presynaptic terminals to that in the cell bodies and axons in early PD patients using [18F](E)‐N‐(3‐iodoprop‐2‐enyl)‐2b‐carbofluoroethoxy‐3b‐(4′‐methyl‐phenyl) nortropane ([18F]FE‐PE2I) and high‐resolution PET. Methods: A total of 20 early PD patients (15 men/5 women, 62 ± 8 years) and 20 controls (15 men/5 women, 62 ± 7 years) underwent high‐resolution [18F]FE‐PE2I PET. Dopamine transporter protein availability was estimated for the different nigro‐striatal regions and expressed as nondisplaceable binding potential values. Results: When compared with controls, the binding potential values in PD patients were reduced by 36% to 70% in presynaptic terminals and by 30% in cell bodies. Dopamine transporter availability along the tracts was not different between the 2 groups (controls 0.5 ± 0.1 vs PD 0.4 ± 0.1). Conclusions: This is the first study that examines dopamine transporter protein availability in vivo within the entire nigro‐striatal pathway. The results suggest that at early stages of symptomatic PD a greater loss is observed at the level of the axonal terminals when compared with cell bodies and axons of dopaminergic neurons. The findings suggest a relative preservation of cell bodies in early PD, which might be relevant for novel disease‐modifying strategies. © 2018 International Parkinson and Movement Disorder Society